IDENTIFICATION OF DEPRESSION IN THE ELDERLY - Rindayati Rindayati; Abd Nasir; Makhfudli Makhfudli; Ali Sairozi; Andini Wulan Sari (Journal of Vocational Nursing, 2023)
Introduction: The elderly is someone who experiences biological, psychological, social, and spiritual decline which can affect mood and lead to depression. This study aims to identify the incidence of depression in the elderly. Methods: This study uses a quantitative design with a descriptive approach. The population is the elderly at the Gresik Alun-Alun Health Center in March 2022, taking samples using purposive sampling were obtained from 61 respondents. Data collection used the Geriatric Depression Scale (GDS) instrument. The research variable is the incidence of depression. Ethical Approval by the Faculty of Health, University of Muhammadiyah Gresik number 068/KET/II.3.UMG/KEP/A/2022. Data analysis using descriptive analysis. Results: Research shows that 49% of the elderly are not depressed, 24% are mildly depressed, 15% are moderately depressed, and very few are severely depressed 11%. Conclusions: Depression as one of the effects of the aging process is significant to be recognized early by using the Geriatric Depression Scale. Non-pharmacological prevention of depression with regular physical exercise is highly recommended.